2011
DOI: 10.1007/s10555-011-9291-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapy innovations: tyrosine kinase inhibitors for the treatment of pancreatic neuroendocrine tumors

Abstract: Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) show limited sensitivity to cytotoxic agents, requiring the search for novel therapies. Recently, data from a phase III trial demonstrated that sunitinib produces a clinically significant improvement in progression-free survival in patients with unresectable, advanced, or metastatic GEP-NETs. Based on this finding, sunitinib became the first targeted drug approved for the treatment of GEP-NETs, paving the way for the approval of other anticancer agents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 39 publications
(42 reference statements)
1
23
0
Order By: Relevance
“…This novel finding may have an immediate clinical application for distinguishing metastatic pancreatic endocrine tumors from other well-differentiated neuroendocrine carcinomas given that there are therapies (tyrosine kinase and mTOR inhibitors) specifically approved for pancreatic tumors. [8][9][10] In addition, a subset of 15 genes within the 92-gene assay panel showed promising discriminatory ability to subclassify the tumor site of origin of neuroendocrine tumors. Further investigation of these genes may have diagnostic and theranostic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel finding may have an immediate clinical application for distinguishing metastatic pancreatic endocrine tumors from other well-differentiated neuroendocrine carcinomas given that there are therapies (tyrosine kinase and mTOR inhibitors) specifically approved for pancreatic tumors. [8][9][10] In addition, a subset of 15 genes within the 92-gene assay panel showed promising discriminatory ability to subclassify the tumor site of origin of neuroendocrine tumors. Further investigation of these genes may have diagnostic and theranostic value.…”
Section: Discussionmentioning
confidence: 99%
“…The site of origin for neuroendocrine carcinoma has become increasingly important for grading/staging purposes, 1,2 for new clinical management guidelines, [3][4][5][6][7] and for primary site-specific targeted therapy. [8][9][10] When a primary site cannot be identified, tumors generally are treated according to the presumed aggressiveness of the tumor, as determined by a combination of the tumor grade [11][12][13][14] and available clinical and radiographic information about tumor metabolism. 14 Because neuroendocrine carcinoma subtyping for site of origin is critical for clinical management, research has been dedicated to finding site and subtype-specific diagnostic markers.…”
mentioning
confidence: 99%
“…The encouraging results obtained in an early, non-randomized trial enrolling patients with either pancreatic or intestinal NET [51] have been confirmed by a large, multicenter, randomized trial restricted to progressive pancreatic NETs [52]. Studies using other anti-angiogenic tyrosine kinase inhibitors, such as sorafenib, which targets VEGFR2 and VEGFR3, are currently in progress [53]. Concerns have been raised about the fact that most of the tyrosine kinase inhibitors currently available in clinical practice induce only a partial inhibition of VEGF signaling: sunitinib does not interact with VEGFR3 (involved mainly in lymphangiogenesis) and sorafenib does not interact with VEGFR1.…”
Section: Anti-angiogenic Treatments In Netsmentioning
confidence: 99%
“…carcinoids is regulated by the influence of VEGF pathway (Kulke 2008, Raymond et al 2011b. VEGF family is formed by six different members: VEGF-A, -B, -C, -D, -E and placental growth factor (PIGF), with different roles in angiogenesis.…”
Section: Vegf-targeted Therapy Angiogenesis In Pnets Andmentioning
confidence: 99%
“…It has a dual effect since it can inhibit a component of the RAF/MEK/ERK signaling pathway, Raf-1, which controls proliferation and cell division. On the other hand, it can also inhibit VEGFR2-3 and PDGFRβ signaling pathway, thus inhibiting angiogenesis (Llovet et al 2008, Ivy et al 2009, Raymond et al 2011b. In a phase II clinical trial, sorafenib demonstrated a partial response of 10% in patients with progressive metastatic NETs (NCT00131911).…”
Section: Vegf-targeted Therapy Angiogenesis In Pnets Andmentioning
confidence: 99%